Self-sensing properties of Engineered Cementitious Composites - Huang, Yi (2020)
The piezoresistivity of cement-based material has already been investigated, but mainly restricted to compressive stress sensing due to brittleness of concrete. Conversely, Engineered Cementitious Composites (ECC) presents superb tensile ductility and pseudo strain-hardening property, which offers unique opportunity for exploring sensing of tensile stress/strain. In this paper, Carbon Black (CB) and supplementary cementitious materials (SCM) were incorporated into ECC to decrease the bulk resistivity and simultaneously acquire high tensile ductility. The resistance of ECC, high fly ash (HFA)-ECC and CB-ECC was measured through a two-probe method under uniaxial tension test. All specimens exhibited increase of resistivity once cracks occurred between two electrodes. The fractional Gauge Factor (GF) in strain-hardening segment was calculated and the relationship of GF and tensile strain was experimentally investigated, which could be potentially utilized in the field of structural health monitoring to enhance the safety of concrete infrastructures.